2016
DOI: 10.1021/acsami.6b05390
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of Self-Healing Nanofiber-based Composites: Static Test and Subcritical Crack Propagation

Abstract: Here, we studied the self-healing of composite materials filled with epoxy-containing nanofibers. An initial incision in the middle of a composite sample stretched in a static fatigue test can result in either crack propagation or healing. In this study, crack evolution was observed in real time. A binary epoxy, which acted as a self-healing agent, was encapsulated in two separate types of interwoven nano/microfibers formed by dual-solution blowing, with the core containing either epoxy or hardener and the she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…So far, fatigue resistance of self-healing polymers and polymer composites has not been extensively studied. Moreover, healing speed is not the main concern of these available works [35][36][37][38][39][40][41][42][43]. In this context, the present investigation might add to the researches in this area.…”
Section: Introductionmentioning
confidence: 90%
“…So far, fatigue resistance of self-healing polymers and polymer composites has not been extensively studied. Moreover, healing speed is not the main concern of these available works [35][36][37][38][39][40][41][42][43]. In this context, the present investigation might add to the researches in this area.…”
Section: Introductionmentioning
confidence: 90%
“…They showed that the incorporation aforementioned C/S nanofibers, containing healing agents, in a conventional carbon/epoxy composite not only led to fabricating a self‐healing polymer matrix composite but also improved mechanical properties of the host composite. Lee et al . also employed a solution‐blown method to encapsulate two part epoxy resin and its curing agent via PVDF/PEO blend shell.…”
Section: C/s Nanofibersmentioning
confidence: 99%
“…These tubes may have some reinforcing effect on the polymer, but it is likely that their net effect will be to reduce strength. Recently, various other approaches have been used to create inbuilt vascular‐type systems, which have achieved impressive levels of damage reduction and life extension . See, for example, Fig.…”
Section: Opportunities For Biomimeticsmentioning
confidence: 99%
“…Recently, various other approaches have been used to create inbuilt vascular-type systems, which have achieved impressive levels of damage reduction and life extension. 64,65 See, for example, Fig. 10 showing repair in a vascular-type structure incorporated into a fibre reinforced polymer.…”
Section: O P P O R T U N I T I E S F O R B I O M I M E T I C Smentioning
confidence: 99%